Nuova definizione di spazi abitativi all’interno del Santa Maria della Scala di Siena tra ‘300 e ‘400 : storia e archeologia - Tixier, Benjamin; Causarano, Marie-Ange; Salvadori, Frank; Sordini, Beatrice (CCSD, 2006)
International audience